Mettl3-mediated m ^6A regulates spermatogonial differentia- tion and meiosis initiation - Kai Xu Ying- Yang Gui-Hai Feng Bao-Fa Sun Jun-Qing Chen Yu-Fei Li Yu-Sheng Chen Xin-Xin Zhang Chen-Xin Wang Li-Yuan Jiang Chao Liu Ze-Yu Zhang Xiu-Jie Wang Qi Zhou Yun-Gui Yang Wei Li (细胞研究：英文版, 2017)
METTL3 catalyzes the formation of N%methyl-adenosine （m6A） which has important roles in regulating various biological processes. However, the in vivo function of Mettl3 remains largely unknown in mammals. Here we gener- ated germ cell-specific Mettl3 knockout mice and demonstrated that Mettl3 was essential for male fertility and sper- matogenesis. The ablation of Mettl3 in germ cells severely inhibited spermatogonial differentiation and blocked the initiation of meiosis. Transcriptome and m6A profiling analysis revealed that genes functioning in spermatogenesis had altered profiles of expression and alternative splicing. Our findings provide novel insights into the function and regulatory mechanisms of MettD-mediated m6A modification in spermatogenesis and reproduction in mammals.